PENERAPAN DESAIN ERGONOMIS MESIN POLES UNTUK KERAJINAN PERAK “UNGGA CREATIVE) UNTUK MENUNJANG PARIWISATA DI DESA UNGGA, KECAMATAN PRAYA BARAT DAYA, KABUPATEN LOMBOK TENGAH - I Made Adi Sayoga; Made Wijana; I Nyoman Nugraha Ardana Putra; I Wayan Joniarta; Rizky Fathullah; Ilham Maulana Akbar (Jurnal Abdi Insani, 2023)
Ungga Village, Praya Barat Daya District, is a well-known silver craft center in Central Lombok. Featured products are: brooches, rings, studs, hairpins, suweng, pendants, bracelets and brooches-pendants. The jewelry is made from a combination of pearl shells which are shaped into oval, round, oblong, rectangular, triangular and half round shapes and then tied/framed with silver ornaments. PKM partner "Ungga Creative" with owner Mr Farid. The problem encountered in SMEs in the production sector is that the working position of the product polishing section is done by sitting cross-legged on the floor, so it is not comfortable for working conditions for more than 1 hour. The field of management is financial management that has not been organized so that business conditions cannot be analyzed as profit or loss. The PKM program provides a solution to SMEs for the inconvenience of working when polishing silver crafts, by designing and designing a polishing table that can be used comfortably and safely. Solutions for the field of financial management are carried out by providing training and assistance in financial management for SME owners. The steps that have been taken are designing a polishing machine based on ergonomic concepts using anthropometric data from employees. So you get the size of the silver craft polishing machine table which is designed with (dimensions: table height 60 cm, table top cover height 40 cm table length 75 cm table width 50 cm. Includes Flash-250C polishing grinder machine power 220/50 Hz 0, 25 HP 2870 rpm. The polishing machine has been handed over to PKM partners and has been able to increase partner productivity by up to 30% because the polishing process can be 2x faster than the previous work method.